Heterosis and combining ability for bushy and butternut traits in pumpkin (Cucurbita moschata) - SINGH, NISHAN; SIDHU, MOHINDER KAUR; DHATT, AJMER SINGH (The Indian Journal of Agricultural Sciences, 2018)
The improvement of pumpkin(Cucurbita moschata Duch ex Poir.) for intensive cultivation necessitates genetic studies, wherein, heterosis and combing ability were studied in half di-allel fashion involving bushy plants and butternut fruits. The genotypes, P-3621 was best general combiner for short vine, internode, equatorial diameter and high fruit shape index, P-6242 for pulp thickness, P-2211 for number of primary branches, P-10224 for polar diameter as well as vegetative growth and P-1343 for petiole length. However, high specific combining ability (SCA) in P-10224 × P-6242, PS × P-6242, P-41212 × P-2211, PS × P-364, P-41212 × P-6242, P-10224 × P-2211 revealed the occurrence of both additive and non-additive gene effects with the predominance of non-additive effects (σ2SCA/ σ2GCA >1) in the inheritance of bushy and butternut traits, which can be exploited through heterosis breeding and recurrent selection in pumpkin. The hybrids, P-3621 × P-2211, P-6711 × P-2211 and P-6711 × P-6242 had high pulp thickness as well as comparable yield potential with the check hybrids and could be exploited for commercial cultivation.